Risk factors for bat contact and consumption behaviors in Thailand; a quantitative study - Kanokwan Suwannarong; Sutin Chanabun; Phitsanuruk Kanthawee; Santisith Khiewkhern; Paisit Boonyakawee; Kangsadal Suwannarong; Chutarat Saengkul; Nisachon Bubpa; Alongkorn Amonsin (BMC, 2020)
Abstract Background Bats serve as an important reservoir for emerging infectious diseases. Bat contact and consumption, which persists in Asia, poses risks for the transmission of bat-borne infections. Methods An analytical cross-sectional survey for risk factors associated with bat contact and consumption behaviors was conducted in ten provinces of Thailand from May 2016 to December 2017. A standardized questionnaire administered through face-to-face interviews was used to collect information from 626 villagers who lived in or nearby areas of high bat density. The questionnaire contained 23 independent variables related to sociodemographic, knowledge, attitudes, practices, and perceptions. Results The respondents (n = 626) were 285 females and 341 males, mean age of respondents was 47.58 years-old and lived in rural setting. Our results showed that 36.42% of respondents (n1 = 228) in 10 provinces reported bat contact during the past 6 months. Furthermore, 15.34% of respondents (n2 = 96) in 9 out of 10 provinces reported of having consumed bat meat in the past 6 months. Risk factors for bat contact included sex (male) (OR = 1.56, 95% CI 1.09-2.28), educational attainment (lower than secondary school) (OR = 1.45, 95% CI 1.02-2.18), and the consideration of bats as being economically beneficial to the community (OR = 3.18, 95% CI 2.03-4.97), while agriculture-related occupation (OR = 0.54, 95% CI 0.37-0.79), knowledge that it is safe to eat bats (OR = 0.58, 95% CI 0.37-0.93), practice of allowing children to play with bats (OR = 0.65, 95% CI 0.44-0.96), and attitude of feeling safe in areas where bats live (OR = 0.56, 95% CI 0.38-0.86) were statistically significant protective factors against bat contact. Risk factors for bat consumption included sex (male) (OR = 2.48, 95% CI 1.49-4.11) and educational attainment (lower than secondary school) (OR = 2.21, 95% CI 1.27-3.85), while knowledge of whether bats are safe to eat (OR = 0.04, 95% CI 0.01-0.25), knowledge of whether there are laws pertaining to hunting bats for consumption (OR = 0.35, 95% CI 0.18-0.71), and the practice of allowing children to play with bats (OR = 0.51, 95% CI 0.31-0.81) were statistically significant protective factors against bat consumption. Conclusions This study provides a better understanding of the sociodemographic factors, knowledge, attitudes, perceptions and practices that might influence bat contact and bat consumption behaviors. Information on risk factors can be used for the development of appropriate education and communication interventions to promote proper knowledge, attitudes and practices regarding bats and bat-borne zoonotic diseases in Thailand and other areas in the Southeast Asia region with similar environmental and cultural characteristics.